Neuroradiologic-Pathologic Correlation in a Neurenteric Cyst of the Clivus - Kapoor, Vibhu; Johnson, Douglas R.; Fukui, Melanie B.; Rothfus, William E.; Jho, Hae D. (American Journal of Neuroradiology, 2002)
Summary: A 28-year-old woman presented with left-sided frontotemporal headache lasting 6 wk. Head CT and MR imaging revealed a clival mass, which was interpreted as a chondrosarcoma. The lesion was removed at endoscopic endonasal surgery; histologic and immunohistochemical findings proved it to be neurenteric cyst. On CT scans, the lesion was lytic, with an intact cortex; it was uniformly hyperintense relative to gray matter on T1-weighted MR images and iso- to hypointense relative to CSF on T2-weighted MR images.